2008
DOI: 10.1364/ol.33.000651
|View full text |Cite
|
Sign up to set email alerts
|

Pulse-duration dependency of femtosecond laser refractive index modification in poly(methyl methacrylate)

Abstract: Refractive index modification of pure poly(methyl methacrylate) (PMMA) is investigated as a function of pulse duration using femtosecond lasers at 800 and 387 nm wavelength. It is observed that at 800 nm, the refractive index is modified more efficiently as the pulse duration decreases below 100 fs, whereas at 387 nm, efficient index modification is accomplished with longer, 180 fs pulses. Results suggest that three- and two-photon absorption is responsible for modification of pure PMMA at 800 nm and 387 nm, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 11 publications
0
24
0
2
Order By: Relevance
“…This implies that the nonlinear process involves at least three photons being responsible for structural modification at the focal volume [10]. Three possible mechanisms [1,21] such as tunnelling, intermediate and multiphoton ionizations are likely to take place when transparent material interacts with femtosecond pulses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that the nonlinear process involves at least three photons being responsible for structural modification at the focal volume [10]. Three possible mechanisms [1,21] such as tunnelling, intermediate and multiphoton ionizations are likely to take place when transparent material interacts with femtosecond pulses.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most important applications of this ability to modify the refractive index (RI) is in the field of photonics [4][5][6][7]. A variety of three-dimensional structures such as waveguides, couplers and gratings have been fabricated in PMMA and PDMS, which are useful for photonic and microfluidic applications [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. A comprehensive understanding of the interaction of femtosecond pulses with these materials with particular attention to their pulse duration, energies, shapes, focussing conditions etc.…”
Section: Introductionmentioning
confidence: 99%
“…The energy of an 800 nm photon corresponds to 1.55 eV while the optical band gap of pure PMMA being 4.58 eV implies that the nonlinear process involving at least three photons is responsible for structural modification at the focal volume [33]. Schaffer et al [34] have shown that there are three possible mechanisms viz.…”
Section: Methodsmentioning
confidence: 99%
“…The fundamental output from a Spectra-Physiscs Spitfire Ti:Sapphire fs laser located in the Photon Science Institute at the University of Manchester with repetition rate of 1 kHz, maximum pulse energy of 3 mJ and pulse duration of 100 fs, was measured using a scanning autocorrelator. The 6 mm diameter laser beam was attenuated by a diffractive optic attenuator and wavelength halved to 400 nm using a BBO crystal, chosen because 400nm had the potential to modify refractive index via 2-photon absorption coupled with smaller feature size 8 …”
Section: Methodsmentioning
confidence: 99%